POTENSI SERAPAN KARBONDIOKSIDA BEBERAPA JENIS DAUN TANAMAN DI JALUR HIJAU JALAN RAYA PAJAJARAN, BOGOR - Mohamad Iqbal; Rachmad Hermawan; Endes N Dahlan (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2015)
The increment of CO2 concentration can effectively be controlled by the development of urban forest through selection of plants that have high potential CO2 sequestration. This research aims to obtain data on the potential CO2 sequestration by leaves of nine species of plants in green belt of Pajajaran Street, Bogor. Primary data was collected through field survey and laboratory analysis of leaf samples using the method of carbohydrates. Case and literature studies were conducted to obtain secondary data from the agency or the relevant literature, especially the results of studies with similar cases. Other data that were collected consisted of total leaves and leaf area. Results showed has the potential CO2 sequestration per leaf highest of 11.86 tonnes/leaf/year. Additionally, and C. manghas F. elastica S. macrophylla also has CO2 sequestration rate are relatively well compared to other plant respectively of 3.83 tonnes/leaf/year and 2.51 tonnes/leaf/year. The inherent factors that determine the potential CO sequestration is leaf width, leaf thickness, greeness of leaves, number of leaves and water content. While external factor among other places plant life, the availability of water and mineral nutrients, as well as the infuence of light and temperature.